Dynamitage cocasse de l’anthropomorphisme dans quelques satires contemporaines - Laetitia Pasquet (Sillages Critiques)
The tradition of satirical representation has granted animals the status of a comparer, from which stems a system of analogies between human flaws and (alledged) animal habits. Contemporary plays and performances shift this anthropomorphic prism, making it more radical, fit for representing horror (and not mere flaws). The system of analogies thus implodes, implying the demise of stability, meaning and harmony. Of all animals, man thus seems to be the least human one. This shift paves the way for a new scenic and verbal representation of animals in the poetic wild, liberated from the chains of meaningful clarity and allegory. The satirical prism is thus replaced by an uncanny, awkward form of comedy that no longer claims to convey a meaning and cause spectators to smile reassuringly, for spectators are no longer at the top of God’s creation. The plays by Steven Berkoff (Decadence - 1981), Gregory Motton (Cat and Mouse Sheep – 1998), Caryl Churchill (Far Away - 2001) and the 2008 mime show by Geoff Sobelle and Charlotte Ford (Flesh and Blood & Fish and Fowl) all illustrate this shift in satirical anthropomorphism. Their bestiary shows the collapse of metaphorical stability and in the light of Derrida’s concept of ‘carnophallogocentrism’ (which deconstructs the supremacy of reason, the reification of animal bodies at once), they stage not only the demise of anthropomorphism, but also the very grounds of the definition of humanity.